2017
DOI: 10.1016/j.jpeds.2016.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Extubation Failure after Neonatal Cardiac Surgery: A Multicenter Analysis

Abstract: Objectives: To describe the epidemiology of extubation failure and identify risk factors for its occurrence in a multicenter population of neonates undergoing surgery for congenital heart disease. Study Design:We conducted a prospective observational study of neonates ≤ 30 days of age who underwent cardiac surgery at seven centers within the United States in 2015. Extubation failure was defined as reintubation within 72 hours of the first planned extubation. Risk factors were identified using multivariable log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
46
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 27 publications
6
46
2
Order By: Relevance
“…The study was a retrospective multicenter cohort study. We collected additional data on neonates who had previously been prospectively enrolled in an observational study examining extubation failure after neonatal cardiac surgery from January 1, 2015 through December 31, 2015 (11…”
Section: Design and Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was a retrospective multicenter cohort study. We collected additional data on neonates who had previously been prospectively enrolled in an observational study examining extubation failure after neonatal cardiac surgery from January 1, 2015 through December 31, 2015 (11…”
Section: Design and Settingmentioning
confidence: 99%
“…For this study, we sought to perform the first multicenter validation of the VVR score utilizing a dataset containing neonates who underwent cardiac surgery at seven tertiary care centers within the United States (11). We hypothesized that the VVR would be a reliable predictor of outcome in this patient population and continue to outperform more traditional measures of disease complexity and severity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that extubation failure in children with cardiac disease is a poor prognostic sign associated with a higher mortality. 2,3 Neonates in particular have a higher rate of extubation failure (12 %) as compared to older children. [3][4][5] Reported rates of extubation failure after neonatal cardiac surgery range from 5 to 23 %.…”
mentioning
confidence: 99%
“…2,3 Neonates in particular have a higher rate of extubation failure (12 %) as compared to older children. [3][4][5] Reported rates of extubation failure after neonatal cardiac surgery range from 5 to 23 %. 3,5,6 Common indicators utilised for assessing extubation readiness following congenital heart surgery include subjective and objective measures of neuromuscular function and oxygenation and ventilation and indirect markers of adequate cardiac output.…”
mentioning
confidence: 99%
See 1 more Smart Citation